The Meaning of Solidarity in Catholic Social Teaching. Issue 1 (1st January 2014) - Beyer, Gerald J.; Peter Henriot, SJ
Abstract Solidarity has become a central concept in Christian ethics. Although solidarity or analogous concepts can be found in other Christian traditions, as well as other religious and philosophical systems of ethics, the Catholic social tradition has perhaps most fully developed a concept of solidarity over the last century. This article contends that solidarity as conceived in Catholic social teaching (CST) provides a robust and useful understanding of the social obligations of individuals, communities, institutions, and nations. As a general overview of the concept of solidarity in CST, the article elucidates its biblical, theological and experiential foundations, its historical antecedents, and the goals, methods and scope of solidarity. The article also describes contemporary applications of the Catholic ethic of solidarity, and theoretical and practical challenges to its realization.